ANALISIS PERUBAHAN ALOKASI BELANJA DALAM ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBA) PROVINSI NAGGROE ACEH DARUSSALAM - Jhon Andra Asmara (Program Magister Akuntansi Unsyiah, 2010)
This study analyzes changes in the Government of Aceh APBA using samples and data sourced from APBA-law documents the government change in Aceh, fiscal year 2006, 2007 and 2008. The data used is purely budgetary data and changing budget allocations for indirect spending and direct spending, which is kind of personnel expenditure, expenditure for goods and services, and capital expenditure, as well as the data is in SILPA research do with Why Based on the results of data analysis and discussion can be concluded that the Personnel expenditures significantly positively correlated with purchases of goods and services, but not correlated with capital expenditures, changes in regional budgets (APBA-P). Purchase of goods and services does not necessarily correlate with the magnitude of capital expenditures and Silpa last year did not affect the changes in the allocation and type of SKPA ceiling SKPA shopping. Keyword; Budget, Revenue, Expenditure, Local Government